Cell Wall Remodeling in Abscission Zone Cells during Ethylene-Promoted Fruit Abscission in Citrus - Merelo, Paz; Agustí, Javier; Arbona, Vicent; Costa, Mário L.; Estornell, Leandro H.; Gómez-Cadenas, Aurelio; Coimbra, Silvia; Gómez, María D.; Pérez-Amador, Miguel A.; Domingo, Concha; Talón, Manuel; Tadeo, Francisco R. (Frontiers in Plant Science, 2017)
Abscission is a cell separation process by which plants can shed organs such as fruits, leaves or flowers. The process takes place in specific locations termed abscission zones. In fruit crops like citrus, fruit abscission represents a high percentage of annual yield losses. Thus, understanding the molecular regulation of abscission is of capital relevance to control production. To identify genes preferentially expressed within the citrus fruit abscission zone (AZ-C), we performed a comparative transcriptomics assay at the cell type resolution level between the AZ-C and adjacent fruit rind cells (non-abscising tissue) during ethylene-promoted abscission. Our strategy combined laser microdissection with microarray analysis. Cell wall modification-related gene families displayed prominent representation in the AZ-C. Phylogenetic analyses of such gene families revealed a link between phylogenetic proximity and expression pattern during abscission suggesting highly conserved roles for specific members of these families in abscission. Our transcriptomic data was validated with (and strongly supported by) a parallel approach consisting on anatomical, histochemical and biochemical analyses on the AZ-C during fruit abscission. Our work identifies genes potentially involved in organ abscission and provides relevant data for future biotechnology approaches aimed at controlling such crucial process for citrus yield.